Inadequate toothbrushing practice and associated factors among in-school adolescents in Malaysia: Findings from Global School Health Survey (GSHS) 2017 - Mohamad Fuad Mohamad Anuar; Nurulasmak Mohamed; S. Maria Awaluddin; Habibah Yacob (PLoS ONE, 2025)
Introduction Inadequate toothbrushing practice is define as brushing teeth less than two times per day. Inadequate toothbrushing during adolescence can lead to oral health problems and disease burden in adults. Moreover, inadequate practice can lead to low quality of life and inadequate self-esteem. Objective This study aimed to determine the prevalence of inadequate toothbrushing practice among adolescents aged 13 to 17 years in Malaysia and its association with sociodemographic and other related risky lifestyles. Method This study was part of a national cross-sectional study, Global School Health Survey 2017. 27,497 students were agreed to participate in this study, with response of 89.2%. A validated self-administered bilingual, comprised of topics related to sociodemographic as well as adolescent health and risky lifestyles; substance use (alcohol, drug, smoking cigarettes), eating patterns, hygiene (inclusive of oral and hand hygiene), mental health status, lack of peer and parental/guardian support, truancy, physical activity, and body mass index (BMI). Analysis was performed using IBM SPSS for Windows version 26.0 involving complex sampling analysis and logistic regression. Results A total of 12.7% (95% CI: 11.8–13.6) of in-school adolescents had inadequate toothbrushing practices. Higher prevalence of inadequate toothbrushing were found among male, Indian, had ever drug use, had three or more lack of protective factors and had inadequate hand hygiene practices. Adolescents who had inadequate toothbrushing were significantly higher odd among males, Indian ethnic, ever drug use, inadequate hand hygiene practices and adolescents who had three or more lack of peer and parental/guardian support. Conclusion Approximately 1 out of 10 adolescents had inadequate toothbrushing practices with several factors associated, such as male gender, Indian ethnicity, inadequate hand hygiene, ever drug use and lack of protective factors are identified to be associated. By emphasizing the significance of frequent brushing, we can encourage positive changes and reduce the burden of preventable dental problems on adolescents.